Sex-Specific Transcriptomic Signatures in Brain Regions Critical for Neuropathic Pain-Induced Depression - Dai, Weiping; Huang, Shuying; Luo, Yuan; Cheng, Xin; Xia, Pei; Yang, Mengqian; Zhao, Panwu; Zhang, Yingying; Lin, Wei-Jye; Ye, Xiaojing (Frontiers in Molecular Neuroscience, 2022)
Neuropathic pain is a chronic debilitating condition with a high comorbidity with depression. Clinical reports and animal studies have suggested that both the medial prefrontal cortex (mPFC) and the anterior cingulate cortex (ACC) are critically implicated in regulating the affective symptoms of neuropathic pain. Neuropathic pain induces differential long-term structural, functional, and biochemical changes in both regions, which are thought to be regulated by multiple waves of gene transcription. However, the differences in the transcriptomic profiles changed by neuropathic pain between these regions are largely unknown. Furthermore, women are more susceptible to pain and depression than men. The molecular mechanisms underlying this sexual dimorphism remain to be explored. Here, we performed RNA sequencing and analyzed the transcriptomic profiles of the mPFC and ACC of female and male mice at 2 weeks after spared nerve injury (SNI), an early time point when the mice began to show mild depressive symptoms. Our results showed that the SNI-induced transcriptomic changes in female and male mice were largely distinct. Interestingly, the female mice exhibited more robust transcriptomic changes in the ACC than male, whereas the opposite pattern occurred in the mPFC. Cell type enrichment analyses revealed that the differentially expressed genes involved genes enriched in neurons, various types of glia and endothelial cells. We further performed gene set enrichment analysis (GSEA), which revealed significant de-enrichment of myelin sheath development in both female and male mPFC after SNI. In the female ACC, gene sets for synaptic organization were enriched, and gene sets for extracellular matrix were de-enriched after SNI, while such signatures were absent in male ACC. Collectively, these findings revealed region-specific and sexual dimorphism at the transcriptional levels induced by neuropathic pain, and provided novel therapeutic targets for chronic pain and its associated affective disorders.